(untitled) (Minerva. Revista de Filología Clásica, 2021)
Reseña de Rosario López Gregoris y Cristóbal Macías Villalobos (eds.), The Hero Reloaded. The Reinvention of the Classical Hero in Contemporary Mass Media, Ámsterdam-Filadelfia, John Benjamins Publishing Company, XIV + 160 páginas, ISBN 978-90-272-0495-0